Evaluation and molecular characterization of 3K rice (Oryza sativa) germplasm subset for blast resistance - DILEEP KUMAR G D; ABDUL FIYAZ R; KASARLA CHAITHANYA; SAHITHI MORE; SHIVANI D; SUNDARAM R M (The Indian Journal of Agricultural Sciences)
Rice (Oryza sativa L.) is one of the most widely cultivated crop species in the world affected by many biotic stresses. Blast, a major biotic constraint in lowland and high altitude grown rice led to inconsistent yields in many parts of India and world. The present study was carried out during 2023 at ICAR-Indian Institute of Rice Research, Hyderabad, Telangana to identify blast resistant lines from 50 selected superior genotypes from 3K germplasm lines collected from Internation Rice Research Institute, Philippines. These lines were screened against SPI-40 blast isolate in uniform blast nursery to identify resistant lines during wet and dry seasons of 2023. Out of 50 lines, 22 were found to be resistant and genotyped using a set of 12 blast-linked/specific SSR markers covering Pi1, Pi2, Pi9, Pi54, Pita, Pi40, Pi33, Pib, Pi20, Pi38, Piz, and Pitp to determine the genetic basis of resistance. Genotyping of the 22 resistant lines confirmed the universality of Pita among the tested lines. Whereas, Pi2 found to be least among the tested lines and Pi40 was completely absent. Results revealed the cause of phenotypic resistance and several combinations of genes which work best against the tested pathotype were identified. The study of genetic diversity revealed that the RM1 marker had the highest PIC value of 0.95, indicating its strong polymorphic nature. Using the Unweighted Pair Group Method with arithmetic mean, the distance-based analysis categorized the accessions into five primary clusters. These resistant genotypes with different genetic cause of resistance can serve their role as source of donors or parental lines in development of blast resistant hybrids or varieties in future breeding programme for crop improvements.